Development of Visuospatial Attention in Typically Developing Children - Ickx, Gaétan; Bleyenheuft, Yannick; Hatem, Samar M. (Frontiers in Psychology, 2017)
The aim of the present study is to investigate the ontogenesis of visuospatial attention in typically developing children and to propose reference values for children for the following six visuospatial attention tests: star cancellation, Ogden figure, reading test, line bisection, proprioceptive pointing and visuo-proprioceptive pointing. Data of 159 children attending primary or secondary school in the Fédération Wallonie Bruxelles (Belgium) were collected. Results showed that the children’s performance on star cancellation, Ogden figure and reading test improved until the age of 13 years, whereas their performance on proprioceptive pointing, visuo-proprioceptive pointing and line bisection was stable with increasing age. These results suggest that the execution of different types of visuospatial attention tasks are not following the same developmental trajectories. This dissociation is strengthened by the lack of correlation observed between tests assessing egocentric and allocentric visuospatial attention, except for the star cancellation test (egocentric) and the Ogden figure copy (ego and allocentric). Reference values are proposed that may be useful to examine children with clinical disorders of visuospatial attention.